Integrating network pharmacology analysis and pharmacodynamic evaluation for exploring the active components and molecular mechanism of moutan seed coat extract to improve cognitive impairment - Wang, Yue; Wu, Xinyan; Yang, Kailin; Liu, Qing; Jiang, Baoping; Yang, Runmei; Xiao, Peigen; He, Chunnian (Frontiers in Pharmacology, 2022)
Paeonia suffruticosa (Moutan) is a traditional medicinal plant in China. Its seed coat is rich in resveratrol oligomer, especially suffruticosol B (SB). Previous studies had shown that the seed coat extracts of Paeonia suffruticosa (PSCE) had good cholinesterase inhibitory activity and neuroprotective effect, but the effective dose range was unknown, and the pharmacodynamic components and molecular mechanism of PSCE had not been discussed. The current study aimed to screen the pharmacodynamic components in PSCE and investigate the improvement effect of PSCE and the selected SB on scopolamine-induced cognitive dysfunction in mice and its mechanism. The results of high-throughput sequencing and bioinformatics analysis showed that suffruticosol B (SB) and trans-gnetin H (GH) might be the main active components of PSCE; PSCE might improve cognitive dysfunction through p53, HIF-1, MAPK, and PI3K-Akt signaling pathways, while SB and GH might improve cognitive dysfunction through HIF-1 signaling pathway. SB and GH had good molecular docking activity with the target of HIF-1 signaling pathway. The pharmacodynamic activities of PSCE and SB were further verified by behavioral experiments. PSCE and SB could improve the recognition ability of familiar and new objects and shorten the escape latency in the Morris Water Maze test (PSCE 120 mg∙kg-1, p<0.05; SB 60 mg∙kg-1, p<0.01); PSCE and SB could increase Ach and GSH levels, enhance the activities of ChAT, SOD and CAT, decrease the levels of IL-1β, IL-6, and TNF-α, and decrease the activity of AChE. In conclusion, the results indicated that PSCE might exert pharmacodynamic activity through multiple components, targets, and pathways, and SB and GH might be the main active components of PSCE. PSCE and SB might improve cognitive dysfunction by regulating cholinergic, antioxidant, and anti-inflammatory effects. These results indicated that PSCE and SB might be potential anti-AD drug candidates, providing a scientific basis for the development and utilization of Moutan bark.